Enhancement of Students' Concept Mastery through Science Learning using Android-based Interactive Multimedia - Nirina, Enik; Fikriyah, Aida; Tamam, Badrut; Putera, Dwi Bagus Rendy Astid; Hartiningsih, Try (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
The low students’ concept mastery in science learning is partly caused by learning media that is less varied and interesting. The learning media used in science learning is only in the form of textbooks, so they cannot visualize difficult and abstract material. This study aims to determine the enhancement of students’ concept mastery through science learning using android-based interactive multimedia. This study is included in a quantitative descriptive by using a one group pretest-posttest design. The sample in this study was 28 students of seventh grade of junior high school at one of schools in Kamal-Bangkalan in the even semester of the 2023/2024 academic year. The research instrument used in this study is a concept mastery test. The data is analysed using the N-Gain technique. Findings indicated that there is enhancement in the students’ concept mastery through science learning using android-based interactive multimedia which reached on 0.40 with moderate criteria. Based on these results, it can be concluded that the science learning with android-based interactive multimedia is able to enhance students' concept mastery on the topic of Indonesia ecology and biodiversity.